(untitled) (Marketing Journal, 2025)
This study investigates the macroeconomic determinants of foreign direct investment (FDI), focusing on the effects of interest rates, inflation, and gross domestic product (GDP) on FDI inflows. Using a log -linear Ordinary Least Squares (OLS) regression mod el and a dataset comprising 33 annual observations, we examine the relationship between the natural logarithms of FDI, interest rates, inflation, and GDP. The results indicate that inflation has a statistically significant and negative impact on FDI, sugge sting that rising inflation discourages investment inflows. Interest rates exhibit a positive and marginally significant effect on FDI, while GDP does not show a statistically meaningful relationship. Variance Inflation Factor (VIF) and Belsley - Kuh-Welsch diagnostics suggest moderate multicollinearity, particularly involving GDP, but not at a level requiring model revision. These findings highlight the sensitivity of FDI to macroeconomic stability, especially inflation, and underscore the importance of main taining a favorable investment climate.